Spatial variation of suicide phenomenon in Dhi Qar governorate - Mudhefer Sahar Al-Kaabi, Assist. Prof. Dr. Murtadha; Nasser Hussein Al-Khakani, . Prof. Dr. Hakim (Basra studies journal, 2023)
The phenomenon of suicide is as old as man and his presence on the surface of the earth, because it is one of the most social, psychological and educational problems that society suffer from, as it is naturally due to aggressive behavior resulting from some emotions and psychological tensions of some people as a result of the pressures of family or community life, which generates a state of psychological imbalance, nervous turmoil and thus affect the mind and body, especially the death of the soul, by its execution by the disturbed person. Iraqi customs and traditions - including the research area - have contributed to preventing the occurrence of suicide as a despicable social characteristic that leaves social effects on the person who commits suicide, and socially stigmatizes whoever commits this act on the one hand, and his family and the society’s view of those neighboring them on the other hand, and therefore it threatens the social and moral fabric. The research is to shed light on the study of the spatial variation of the phenomenon of suicide according to the administrative units of Dhi Qar Governorate for the period from 2015 to 2020, according to the available official data in this regard.